A new scenario for banks: glocal banking. A theoretical approach to propose for Europe. (2017) - Anselmi, Francesco Antonio
In the early 1990s, with the development of information and communication technology (ICT), global banks began looking for a new world consisting of markets rather than relationships through the development of standardised services in the markets. However, in the early 21st century, with the collapse of the speculative bubble and the financial crisis of 2008, which caused financial instability and damaged the real economy, the entire banking system and the market itself suffered profound changes in profitability. Thus, began efforts to develop a new cultural relationship between banks and companies known as 'glocal banking'. These include: studying the needs of customers, planning and providing services, working as a team and using new training methodologies coherent with a new entrepreneurial banking culture based on relationships with small- and medium-sized enterprises (SMEs), which represent both the majority of European and Italian firms (Italian SMEs account for ~99% of the national total).